Contingency factors of marketing-mix standardization german consumer goods companies in central and eastern Europe - Codita, Roxana; SpringerLink (Online service). (Wiesbaden Gabler, 2011)
This study addresses the marketing-mix standardization issue in the Central and Eastern European context. Special consideration is given to the construct of product cultural specificity, for which a new measure is proposed. The newly developed measure exhibits satisfactory levels of reliability, face, convergent and discriminant validity, while further research is required to establish the construct?s nomological validity. Findings reveal that German consumer goods companies adopt a high degree of marketing-mix standardization in Central and Eastern Europe, with product and promotion being the most standardized elements.
Marketing-Mix Standardization in Central and Eastern Europe, its Contingency Factors and Performance Implications; Empirical Conceptualization and Operationalization of the Product Cultural Specificity Construct; PLS Path Analysis
Electronic reproduction.
Keywords: Marketing -- Standards -- Management. -- Germany; Electronic books